Analisis Strategi Pemasaran Dalam Upaya Meningkatkan Jumlah Penerimaan Mahasiswa Baru - Khamdan Suriyok (Ecobuss, 2022)
The research was conducted with the aim of knowing and analyzing marketing strategies in an effort to increase the number of new student admissions. The research was conducted at the Yadika Bangil School of Economics (STIE). Data were collected through observation, document analysis, and interviews. The data analysis technique was carried out using the SWOT analysis method (Strengths, Weaknesses, Opportunities and Threats). The results showed that the more programs there were, the more alternatives students had to choose from. In addition, the programs offered will increase student interest in registering. As well as large financial support for promotion and supported by good quality lecturers, various study programs and affordable prices can increase the number of students. Keyword: Increasing Number of Student, Marketing Strategy, SWOT